Subjective well-being index based on the social right to public health: A comparative study of Mexico, Brazil, Colombia, And Ecuador - Larios Gómez, Emigdio (Horizonte Sanitario, 2026)
Objective: To comparatively analyze the relationship between the effective exercise of social rights to health and the subjective well-being of users of public health services in Mexico, Brazil, Colombia, and Ecuador, from a health marketing perspective focused on public value creation, user experience, institutional trust, and service satisfaction, in order to propose a Subjective Well-Being Index based on the Social Right to Public Health applicable to Latin American contexts. Materials and Methods: Quantitative, deductive, non-experimental, cross-sectional and correlational-explanatory study. Survey of 1,536 adult beneficiaries of public health services (384 per country) in Mexico, Brazil, Colombia and Ecuador. Variables: social rights to health (VI), marketing for health (mediator) and subjective well-being (DV). Analysis using PLS-SEM. Results: The PLS-SEM structural model showed adequate levels of reliability and validity. Hypotheses were confirmed, revealing positive and statistically significant relationships between social rights to health (H1), health marketing (H2), and subjective well-being (H3). Partial mediation validated the Subjective Well-Being Index based on the Social Right to Public Health, demonstrating consistency and comparability across Mexico, Brazil, Colombia, and Ecuador. Conclusions: The study validates the Subjective Well-Being Index based on the Social Right to Public Health as a comparative analytical tool for Mexico, Brazil, Colombia, and Ecuador. The index integrates social rights, health marketing, and subjective well-being, providing scientific evidence on how the guarantee of rights and institutional experience explain well-being in public health services. Keywords: Subjective well-being; Social rights; Right to health; Health marketing.